CXCL8 derived from mesenchymal stromal cells supports survival and proliferation of acute myeloid leukemia cells through the PI3K/AKT pathway - Cheng, Jingying; Li, Ying; Liu, Shiqi; Jiang, Yajing; Ma, Jiao; Wan, Li; Li, Qinghua; Pang, Tianxiang (The FASEB journal, 2019)
The role of proinflammatory cytokines secreted by the bone marrow mesenchymal stromal cells (BM-MSCs) in the progression of acute myeloid leukemia (AML) is poorly understood. We compared C-X-C motif chemokine ligand (CXCL)8 expression levels in the BM-MSCs of patients with AML and normal control subjects and detected significantly higher levels in the former. Furthermore, CXCL8 was up-regulated in cocultures of BM-MSCs and leukemic cell lines compared with either monoculture. CXCL8 expression was significantly higher in MSCs compared with mononuclear cells in patients with de novo AML. To elucidate the function of paracrine CXCL8 in AML, we blocked CXCL8 binding to the C-X-C motif chemokine receptor (CXCR)2 in the AML cells using SB225002. Inhibition of CXCL8/CXCR2 binding decreased proliferation in the AML cells by inducing cell cycle arrest at the G /G phase and apoptosis via decreased AKT phosphorylation. Blocking the PI3K/AKT signaling pathway by a specific inhibitor induced similar apoptosis induction and lower proliferation, suggesting that the PI3K/AKT signaling pathway was also involved in CXCL8 action. Taken together, our findings demonstrate that BM-MSCs are the main source of CXCL8 in the AML bone marrow microenvironment and promote leukemogenesis via the PI3K/AKT signaling pathway, indicating a novel therapeutic target.-Cheng, J., Li, Y., Liu, S., Jiang, Y., Ma, J., Wan, L., Li, Q., Pang, T. CXCL8 derived from mesenchymal stromal cells supports survival and proliferation of acute myeloid leukemia cells through the PI3K/AKT pathway.